2012
DOI: 10.1007/s12541-012-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Temperature distribution in polishing pad during CMP process: Effect of retaining ring

Abstract: Heat generation is inevitable during the chemical mechanical planarization (CMP) process because the mechanical and chemical removal of material is carried out by using abrasives and chemicals in the CMP slurry. In this paper, results obtained from experiments performed on a membrane-type carrier having a retaining ring were used to study the temperature distribution in a polishing pad during the CMP process. To understand and predict the distribution of temperature rise, a kinematical analysis of the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Kim et al 12 showed that the contact area increases with temperature caused by the decrease of asperity hardness due to the temperature elevation. Lee et al 13 showed that the rise of the pad temperature increases the temperature of the slurry flow in the pad-substrate interface. In our experiment, the platen coolant temperature is adjusted from 10 to 30 o C to verify the effect of elevating pad temperature in the process.…”
Section: Platen Coolant Temperaturementioning
confidence: 99%
“…Kim et al 12 showed that the contact area increases with temperature caused by the decrease of asperity hardness due to the temperature elevation. Lee et al 13 showed that the rise of the pad temperature increases the temperature of the slurry flow in the pad-substrate interface. In our experiment, the platen coolant temperature is adjusted from 10 to 30 o C to verify the effect of elevating pad temperature in the process.…”
Section: Platen Coolant Temperaturementioning
confidence: 99%